2016
DOI: 10.1007/s00604-016-1756-0
|View full text |Cite
|
Sign up to set email alerts
|

Porous graphene containing immobilized Ru(II) tris-bipyridyl for use in electrochemiluminescence sensing of tripropylamine

Abstract: Three-dimensional porous graphene (3D-pGR) was used to immobilize Ru(II) tris-bipyridyl [Ru(bpy) 3 2+ ] for electrochemiluminescence (ECL) based sensing of tripropylamine (TPA). The 3D-pGR with interpenetrating porous structures was produced from freeze-drying dispersions containing graphene oxide followed by calcination. Field emission scanning electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy were used to characterize morphologies and the composition of the 3D-pGR. After immobiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the determination of TPA concentration in water is significant for human health and environmental protection [43]. Therefore, the determination of TPA concentration in water is significant for human health and environmental protection [43].…”
Section: Application To Real Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the determination of TPA concentration in water is significant for human health and environmental protection [43]. Therefore, the determination of TPA concentration in water is significant for human health and environmental protection [43].…”
Section: Application To Real Samplesmentioning
confidence: 99%
“…Therefore, the determination of the TPA concentration in water is significant for human health and environmental protection. 43 It is necessary to note that most of traditional ECL assays need high concentrations of TPA (usually up to 100 mM) to obtain good sensitivity, 40,42 while the cloth-based C-WL-ECL assays involve relatively lower concentrations of TPA (Fig. 5(D)).…”
Section: Application To Real Samplesmentioning
confidence: 99%
“…Those nanomaterials with outstanding quantum efficiencies can be directly fabricated and employed as promising ECL emitters for signal transduction or image probing. For those nanomaterials with large specific surface areas or porous nanostructures, such as mesoporous silica nanospheres (MSNs) [10][11][12][13], multiwall carbon nanotubes [14][15][16], graphene oxide [17][18][19][20], Ti 3 C 2 MXene [21][22][23], and Au nanoparticles (NPs) [24], they can be utilized as the carriers to stabilize luminophores and developed as ECL emitters for biosensors. Unlike self-annihilation ECL pathway, a proper coreactant reagent is essentially required for coreactant ECL since it can generate abundant electro-active intermediates to promote the production of excited states, thus achieving stronger ECL intensity [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lin et al reported ECL sensing strategy of tripropylamine using porous graphene. 25 Noman et al established an electrochemical luminescence sensing platform using carbonized pistachio nut shells. 26 Nevertheless, the electrocatalytic activity of pure porous carbon materials is limited by its poor enzyme-like activity.…”
mentioning
confidence: 99%